REPRESENTATION OF THE MEMORIAL CULTURE IN CHECHEN PAINTING (2000-2012) - Nasrudi U. Yarychev; Zarema R. Khamzatova (Russian Studies in Culture and Society, 2023)
The object of the research is the memorial culture in Chechen painting, the subject being its representation in the works of Chechen artists. The purpose of the study is to consider the representation of the phenomenon of memorial memory in the work of Chechen artists. The paintings of national artists of Chechnya served as empirical material in the work. The methodology is based on comparative studies, art history and the system-constructive analysis.